Evolutionary implications of Avian Infectious Bronchitis Virus (AIBV) analysis - Shi, Peng (Cell Res, 2006)
For developing efficient vaccines, it is essential to identify which amino acid changes are most important to the survival of the virus. We investigate the amino acid substitution features in the Avian Infectious Bronchitis Virus (AIBV) antigenic domain of a vaccine serotype (DE072) and a virulent viral strain (GA98) to better understand adaptive evolution of AIBV. In addition, the SARS Coronavirus (SARS-CoV) was also analyzed in the same way. It is interesting to find that extreme comparability exists between AIBV and SARS in amino acid substitution pattern. It suggests that amino acid changes that result in overall shift of residue charge and polarity should be paid special attention to during the development of vaccines.